1990
DOI: 10.1017/s0167676800002087
|View full text |Cite
|
Sign up to set email alerts
|

Entitlement to Maritime Areas of Rocks Which Cannot Sustain Human Habitation or Economic Life of Their Own

Abstract: Article 121 of the 1982 United Nations Convention on the Law of the Sea (LOS Convention) retains the traditional definition of an island as: ‘a naturally formed area of land, surrounded by water, which is above water at high-tide’ (paragraph 1), and attributes to it the same maritime spaces as the mainland. These spaces are at present: the 12 mile territorial sea (TS), the 24 mile contiguous zone (CZ), the continental shelf (CS) and the 200 mile exclusive economic (or fishery) zone (EEZ) (paragraph 2). However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…It is worth noting that one of the judges on the Tribunal, Professor Soons, stated that "if the capacity of an island not sustaining human habitation or economic life at present can be admitted on the basis of past human habitation or economic life, logic would also require admission on the basis of future capacity." 104 Other authors have rightfully suggested that in this regard, modern technology can certainly have a role to play in creating 'economic life' where previously there was none. 105 The fact that the PCA declined to recognize some of the relevant maritime features as islands did not mean that these features are completely unusable for maritime-delimitation purposes.…”
Section: Assessment Of the Award And Its Legal And Practical Implicationsmentioning
confidence: 99%
“…It is worth noting that one of the judges on the Tribunal, Professor Soons, stated that "if the capacity of an island not sustaining human habitation or economic life at present can be admitted on the basis of past human habitation or economic life, logic would also require admission on the basis of future capacity." 104 Other authors have rightfully suggested that in this regard, modern technology can certainly have a role to play in creating 'economic life' where previously there was none. 105 The fact that the PCA declined to recognize some of the relevant maritime features as islands did not mean that these features are completely unusable for maritime-delimitation purposes.…”
Section: Assessment Of the Award And Its Legal And Practical Implicationsmentioning
confidence: 99%
“…It is arguable that if harbour reclamation qualifies as addition to state territory, this opens the possibility of artificially extended islands (rocks) (Kwiatkowska and Soons, 1990).…”
Section: The Spratly Islandsmentioning
confidence: 99%
“…As considerations of equity gives islands various effects in determining entitlements to maritime areas, islands may generate full or partial maritime spaces, or none at all. 35 It is impressive to understand that even an island entitled to full maritime zones under Article 121 may only be given partial effect or no effect at all on delimiting a maritime boundary in accordance with Articles 15, 74 or 83. Why do island status and its effects on delimitation not exactly correspond?…”
Section: A Application Of Article 121 In Maritime Delimitationmentioning
confidence: 99%